Ten2Twenty-Ghana: Study Design and Methods for an Innovative Randomized Controlled Trial with Multiple-Micronutrient–Fortified Biscuits among Adolescent Girls in Northeastern Ghana. Issue 2 (8th January 2021) - Azupogo, Fusta; Abizari, Abdul-Razak; Osendarp, Saskia J M; Feskens, Edith J; Brouwer, Inge D
ABSTRACT: Investing in adolescent girls' nutrition is vital for health and for breaking the intergenerational cycle of malnutrition and deprivation, but limited knowledge on the type, timing, and efficacy of interventions delays progress. We describe the design of a 26-wk randomized placebo-controlled trial with multiple-micronutrient–fortified biscuits (MMBs) among adolescent girls in northeastern Ghana. Apparently healthy, premenarche ( n = 312) and postmenarche ( n = 309) girls (10–17 y) were randomly assigned to receive the following for 5 d/wk: 1 ) MMBs (fortified with 11 vitamins and 7 minerals) or 2 ) unfortified biscuits. Data included plasma micronutrient status, anthropometry, body composition, cognitive function, psychosocial health, fertility, dietary intake, and sociodemographic and socioeconomic covariates, complemented with in-depth interviews ( n = 30) and 4 focus group discussions. We hypothesized an increase in plasma ferritin and retinol-binding protein with a resultant increase in hemoglobin, cognition, vertical height, and psychosocial health. Our study seeks to investigate the efficacy and optimal timing of a multiple-micronutrient food intervention program for adolescent girls. The RCT was registered prospectively with the Netherlands Clinical Trials Register (NL7487).